Strategi Edukasi Masyarakat melalui Penyuluhan Pengelolaan Sampah di Desa Tapos 1 Kecamatan Tenjolaya Kabupaten Bogor - Somantri, Fikri Indriana; Primarni, Amie; Suryana, Agus; Murtafiah, Fifih; Wijaya, Siska Putri; Rahmawati, Dian; Putri, Sardiani; Maulana, Dede; Adawiyah, Siti Robiyatul; Khoeriyah, Siti; Billa, Keisya; Fikri, M. Chairil (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Waste is one of the most pressing environmental issues, occurring not only in urban areas but also in rural areas, including Tapos 1 Village, Bogor Regency. Low public awareness of waste sorting and management leads to widespread indiscriminate waste disposal, which impacts environmental pollution and health. This study aims to analyze community education strategies through outreach activities to increase awareness, participation, and innovation in waste management in Tapos 1 Village. The method used was descriptive qualitative, supported by a literature review. Data were obtained through field observations, informal interviews with residents and village officials, and documentation of outreach activities. These data were then analyzed narratively using an inductive approach. The results showed changes in community behavior following the outreach, including increased awareness of separating organic and inorganic waste, active involvement in community service activities and composting, and the emergence of creative economy initiatives based on recycling. However, challenges remain, particularly related to behavioral inconsistencies and limited infrastructure. This study confirms that participatory outreach is effective in fostering collective awareness, building community engagement, and opening up opportunities for a circular economy. This research contributes to providing an applicable and collaborative educational strategy model to support sustainable village-based waste management.